THE EFFECT OF PROFITABILITY RATIOS ON SHARE PRICES OF PERSERO COMMERCIAL BANKS IN INDONESIA FOR PERIOD 2017-2021 - Nuril Romadhoni; Prihatiningsih Prihatiningsih; Septian Yudha Kusuma (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This study aims to measure the effect of the variables Return On Asset (ROA), Return On Equity (ROE), Net Profit Margin (NPM) on the Stock Price of Persero Commercial Banks in Indonesia in 2017-2021. The number of samples consists of 4 banks obtained using the total sampling technique. The data used is secondary data obtained from the Quarterly Financial Statements published on the official website of PT Bank Negara Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, PT Bank Rakyat Indonesia (Persero) Tbk, and PT Bank Tabungan Negara (Persero) Tbk during of the period 2017-2021. The data analysis model used is multiple linear regression analysis using SPSS 25.00 software. In contrast, hypothesis testing uses data analysis techniques, namely the coefficient of determination (Adjusted R2), F test and t-test. Based on the results of the coefficient of determination test (Adjusted R2), it shows that Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) contribute an influence of 0.36 or 36% to the stock price. In comparison, 0.64 or 64% is explained by other variables outside the research model. F-test results show that Return On Assets (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) simultaneously have a significant effect on stock prices. Based on the results of the t-test shows that the variables Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) partially have a significant effect on the Share Price at Persero Commercial Banks in Indonesia for the period 2017-2021.